The Impact of Latin Alphabet Instruction on Thai Vocabulary Writing Skills and Science Understanding of Thai-Malay Junior High School Students (Study Case at Padung Mat School Narathiwat Thailand - Wiwin Wahyuni Lubis; Eli Marlina Harahap; Happy Sri Rezeki Purba; Isthifa Kemal; Elisa; Suhaimee Paneajeaka (Postgraduate, University of Mataram, 2025)
This study aims to analyze the influence of Latin alphabet usage on the vocabulary writing skills and science understanding of Thai Malay among Mattaeom 1 students at Ban Padungmat School, Thailand. A qualitative descriptive method was employed using participatory observation and documentation techniques on 25 students. The findings reveal that students face significant challenges in writing vocabulary due to differences in graphemic and phonological systems between the Latin alphabet and Thai script. Three dominant types of errors were identified: graphemic errors (72%), phonological errors (80%), and mixed usage of Latin and Thai characters (60%). These errors are influenced by negative transfer from the mother tongue and low adaptation to the Latin script. The study emphasizes the need for a contextual and phonetic-based learning approach in teaching the Latin alphabet to bilingual students. It recommends more intensive phonological and graphemic training to enhance vocabulary writing accuracy in Thai Malay.